First-principles calculations of electronic, optical, phononic and thermodynamic properties of C40-type TMSi2 (TM = Cr, Mo, W) disilicides. (September 2021) - Lu, Yaoping; Duan, Yonghua; Peng, Mingjun; Yi, Jianhong; Li, Caiju
Abstract: To broaden the scope of application of transition metal disilicides and to explore more deeply the potential as novel materials, the first-principles calculations based on density functional theory were performed to investigate the electronic structure and optical, thermodynamic and phononic properties of C40-type CrSi2, MoSi2 and WSi2 disilicides. CrSi2, MoSi2 and WSi2 are indirect bandgap semiconductors with band-gaps of 0.316 eV, 0.058 eV and 0.022 eV, respectively. CrSi2 has the highest anisotropy in optical properties, whereas WSi2 possesses the lowest one. According to the obtained reflectivity, these disilicides can be used as optical shielding devices in the far ultraviolet region. Finally, the phononic properties of the three disilicides indicate that they are dynamically stable, and the Dulong-Petit limit for C V of these disilicides is 75 J/(mol·K). Highlights: The C40-type WSi2 is the most stable compared to C40-type CrSi2 and MoSi2 . Band gaps of CrSi2, MoSi2, and WSi2 are 0.343, 0.058, and 0.022 eV, respectively. The order of optical anisotropy is WSi2 > MoSi2 > CrSi2 . They are potential optical shielding materials for FUV radiation.